Out of fire disaster: dynamics of livelihood strategies of rural community on peatland use and management - Winarno, B.; Rohadi, D.; Herawati, T.; Rahmat, M.; Suwarno, E. (IOP Publishing, 2020)
Rural community in peatland is less concerned actor during the recurrent fire disaster. This disaster has already diminished the source of livelihoods. There is limited information about the dynamics of the livelihoods related to the use of fire in peatland. This paper examines the dynamics of rural livelihoods and the adaptation livelihoods strategies in degraded peatland. Data are collected by field survey, in-depth interview, focus group discussion in three villages at Riau Province and they are analyzed descriptively. Peatland is the only remaining important resource for the rural people after fire disaster. They will select prospective commodities based on their capabilities and access to market. Rural community are more intensive in using the resource of peatland for their livelihoods with the growing interest to several commodities. Recent community livelihoods depend on some certain commodities (palm oil, areca nut, rubber) and tend to conduct expansive and monoculture land use strategy rather than polyculture strategy. Diversification livelihood with adaptive and valuable commodities through trainings, continuous coaching and building business.